Lung cancer and occupational exposures other than cotton dust and endotoxin among women textile workers in Shanghai, China. Issue 6 (3rd December 2010) - Checkoway, H; Ray, R M; Lundin, J I; Astrakianakis, G; Seixas, N S; Camp, J E; Wernli, K J; Fitzgibbons, E D; Li, W; Feng, Z; Gao, D L; Thomas, D B
Abstract : Objectives: Numerous epidemiological studies of lung cancer among textile workers worldwide consistently indicate reduced risks related to cotton dust exposure, presumably due to endotoxin contamination. Our objective was to investigate associations with other exposures potentially related to lung cancer, including wool and synthetic fibre dusts, formaldehyde, silica, dyes and metals, that have only been studied to a limited extent in the textile industry. Methods: We conducted a case–cohort study nested within a cohort of 267 400 women textile workers in Shanghai, China. We compared work assignments and exposure histories of 628 incident lung cancer cases, diagnosed during 1989–1998, with those of a reference subcohort of 3188 workers. We reconstructed exposures with a job–exposure matrix developed specifically for textile factories. Cox proportional hazards modelling was applied to estimate age/smoking-adjusted relative risks (hazard ratios) and risk gradients associated with job assignments and specific agents other than cotton dust and endotoxin. Results: No associations were observed for lung cancer with wool, silk or synthetic fibre dusts, or with most other agents. However, increased risks, although statistically imprecise, were noted for ≥10 years' exposures to silica (adjusted HR 3.5, 95% CI 1.0 to 13) and ≥10 years' exposures to formaldehyde (adjusted HR 2.1, 95% CI 0.4 to 11). Conclusions: Exposures to silica and formaldehyde, although not widespread among the cohort, may have increased lung cancer risk. Silica is an established human lung carcinogen, whereas there is only weak prior evidence supporting an association with formaldehyde. Both exposures warrant consideration as potential lung carcinogens in textile manufacturing.